Using the School Environment to Promote Walking amongst Adolescent Females: A Mixed-Method Study - Carlin, Angela (Children (Basel), 2019)
Schools have the potential to promote physical activity (PA) in adolescents through physical education (PE) and extra-curricular PA. The aims of this study were to firstly understand the experiences of adolescent females who participated in a school-based walking programme (the Walking In ScHools (WISH) study) and secondly, to assess the potential for schools to further promote PA outside of structured PE. A sample of female participants (n = 45, mean age 13.1 years) who participated in the WISH study were randomly selected to participate in focus group discussions, to explore their experiences of the intervention. In addition, an online survey was distributed to all post-primary schools (n = 208) in Northern Ireland to assess the provision of extra-curricular PA and further evaluate the feasibility of the WISH study. In total, six focus groups were conducted. Walking during the school day was viewed as an acceptable form of PA by adolescent females, providing an opportunity to be active with friends, and helped participants overcome barriers previously associated with being active at school. Responding schools (n = 59) identified adolescent females and non-sporty pupils as sub-groups who would benefit most from participation in a school-based walking programme. This study has highlighted that the delivery of a walking programme within the school setting is acceptable, warranted and practically feasible from the point of view of adolescent females and key stakeholders within the school setting.